Perancangan Sistem Informasi Manajemen Risiko Rumah Sakit Berbasis Website - Syabrullah, Andreas; Fibrian, Ivan Dwi; Syaikhuddin, Muhammad Miftakhul (Faculty of Computer Science, University of Jember, 2023)
Risk management was an effort to identify, prioritize, analyze, and reduce potential risks that could occur to patients, visitors, staff, and organizational assets. With risk management, hospitals could implement more effective decision-making to prevent undesirable events from occurring in providing health services. Rumah Sakit Ibu dan Anak Muslimat Jombang did not yet have an integrated risk management system. Risk recording was done manually, which raised various problems. Therefore, to facilitate data management, a system was needed that could make it easier for hospitals to manage risk management as a basis for decision-making. The aim of this research was to design a hospital risk management information system. The design was carried out using the waterfall method and with UML notation. The programming language used was PHP with the help of the Codeigniter framework, and the database used was MySQL. Testing of this system was carried out using blackbox testing. This information system produced 14 features in 19 menus, and the system could be accessed according to different access conditions. The result of this research was the management of hospital risk management using a hospital risk management information system. This system could be used by all hospitals because it was built based on applicable laws and regulations.